Identification Of Oral Bacteria From Subgingival Plaque And The Effect Of Salvadora Persica Extracts On The Growth - Nur Fatimah Zaharah Salehuddin
Oral diseases are commonly found in the human population caused by the accumulation of bacterial plaque. There is still lacking of study regarding types of oral bacteria in the Malaysian population. Streptococcus mutans (S. mutans) is one of oral streptococci which initiate periodontal disease as an early colonizer. Over time, Gram-negative anaerobes become more established, especially Porphyromonas gingivalis (P. gingivalis). Nevertheless, bacteria can develop antibiotic resistance to medicinal drugs over time. However, Salvadora persica (S. persica) or known as miswak is acknowledged significantly due to the presence of bioactive compounds that contain inhibitory activity against oral bacteria. The main objective in this study is to identify oral bacteria from subgingival plaque and determine the antibacterial activities of Salvadora persica Stem Extracts (SPSE) against selected oral bacteria. The specific objective of this study is to identify the type of oral bacteria in subgingival plaque using 16S rRNA sequencing, to determine the antibacterial activities of SPSE against selected oral bacteria and to investigate the phytochemistry compositions of SPSE using Gas Chromatography Mass Spectrometry (GCMS). This study successfully isolated 176 oral bacteria from 10 subgingival plaque samples. A total of 17 oral bacteria had been identified from all samples. About 97 Gram-negative bacteria were successfully isolated from all samples. The majority of the bacteria are Gram-positive which is Streptococcus species and others are Gram-negative bacteria, including P. gingivalis, A. actinomycetemcomitans and K. pneumoniae. SPSE were produced using n-hexane, DCM, acetone, ethanol, and methanol. Antibacterial activities of SPSE-n-hexane, SPSE-DCM, SPSE-acetone, SPSE-ethanol, and SPSE-methanol were determined by performing three different techniques, such as disc diffusion assay (DDA), minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) against S. mutans and P. gingivalis. Gas chromatography mass spectrometry (GCMS) was analysed to investigate the phytochemistry composition in SPSE that can inhibit the growth of S. mutans and P. gingivalis. From the results, there is a significant difference between the type of solvents used in SPSE and the diameter of the inhibition zone for S. mutans and P. gingivalis (p < 0.001). For MIC results, S. mutans were inhibited with SPSE-n-hexane at 3.125 mg/mL. Meanwhile, S. mutans were killed with 6.25 mg/mL of SPSE-n-hexane. In GCMS analysis, the major phytochemical of all extracts was benzoic acid, hexadecanoic acid and octadecanoic acid. In conclusion, S. persica is highly recommended as one of the oral hygiene tools to treat oral diseases due to its effectiveness in inhibiting the growth of oral bacteria.